2022
DOI: 10.3390/biology11121702
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Movement on the Cerebrospinal Fluid Pressure of the American Alligator (Alligator mississippiensis)

Abstract: This study was undertaken to document how the cerebrospinal fluid (CSF) pressure varied during movements and physiological activities. Using surgically implanted pressure catheters; the CSF pressure was recorded from sub-adult American alligators (Alligator mississippiensis) under anesthesia and post-recovery. Pressures were recorded during physiological activities (the cardiac cycle; passive and active ventilation); manual manipulation of the anesthetized animals (foot sweeps; tail oscillations; and body bend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Presumably this continuum of influence is driven predominantly by changes in spinal compliance due to changes in blood pressure within the spinal venous sinus; vascular pressures are the main determinants of compliance in the skull and vertebral canal 6 . Previous studies on Alligator mississippiensis have shown that CSF pressure is influenced by movement 39 , 40 , and that movement-related CSF pulsations asymmetrically propagate across the foramen magnum, presumably due to differential compliance 38 . The present study suggests that the spinal venous sinus plays a key role in modulating the compliance of the spinal dura, and, in this way, can significantly influence the exchange of CSF between the cranial and spinal compartments, and the basic parameters of the CSF pressure wave.…”
Section: Discussionmentioning
confidence: 97%
“…Presumably this continuum of influence is driven predominantly by changes in spinal compliance due to changes in blood pressure within the spinal venous sinus; vascular pressures are the main determinants of compliance in the skull and vertebral canal 6 . Previous studies on Alligator mississippiensis have shown that CSF pressure is influenced by movement 39 , 40 , and that movement-related CSF pulsations asymmetrically propagate across the foramen magnum, presumably due to differential compliance 38 . The present study suggests that the spinal venous sinus plays a key role in modulating the compliance of the spinal dura, and, in this way, can significantly influence the exchange of CSF between the cranial and spinal compartments, and the basic parameters of the CSF pressure wave.…”
Section: Discussionmentioning
confidence: 97%
“…Locomotion in Alligator is driven, as in all other vertebrates, by lower motor (spinal) neurons and the associated spinal neuronal circuitry (El Manira, 2014). Body movements in Alligator create pressure waves within both the CSF (Young & Cramberg, 2022a, 2022b) and the vs (Taylor et al, 2023). The pressures waves within the vs simultaneously convey physiological pressures (e.g., inspiration) to the CSF, differentially propagate pressures along the length of the spinal cord, and influence existing CSF pressure waves by altering dural compliance (English et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…[28,29] Inertial shifts in the CSF of humans have been shown in conjunction with rotation of the head; [38] and recent work has shown a link between natural body movements and CSF pressure dynamics. [40,41] e push/pull trials consistently yielded asymmetric results; the pressure change in the cranial compartment was significantly greater than the pressure change in the spinal compartment [Table 1]. is differential cannot be explained by differential momentum.…”
Section: Discussionmentioning
confidence: 99%